Improving the Performance of DC Microgrids byb Utilizing Adaptive Takagi-Sugeno Model Predictive Control - Hui Hwang Goh, Hui Hwang Goh; Jiahui Kang, Jiahui Kang; Dongdong Zhang, Dongdong Zhang; Hui Liu, Hui Liu; Wei Dai, Wei Dai; Tonni Agustiono Kurniawan, Tonni Agustiono Kurniawan; Kai Chen Goh, Kai Chen Goh (2023)
In naval direct current (DC) microgrids, pulsed power loads (PPLs) are becoming more prominent. A solar system, an energy storage system, and a pulse load coupled directly to the DC bus compose a DC microgrid in this study. For DC microgrids equipped with sonar, radar, and other sensors, pulse load research is crucial. Due to high pulse loads, there is a possibility of severe power pulsation and voltage loss. The original contribution of this paper is that we are able to address the nonlinear problem by applying the Takagi-Sugeno (TS) model formulation for naval DC microgrids. Additionally, we provide a nonlinear power observer for estimating major disturbances affecting DC microgrids. To demonstrate the TS-potential, we examine three approaches for mitigating their negative effects: instantaneous power control (IPC) control, model predictive control (MPC) formulation, and TS-MPC approach with compensated PPLs. The results reveal that the TS-MPC approach with adjusted PPLs effectively shares power and regulates bus voltage under a variety of load conditions, while greatly decreasing detrimental impacts of the pulse load. Additionally, the comparison confirmed the efficiency of this technique.